Fenomena Pesta Pernikahan Adat Dayak di Tengah Keragaman Beragama - Nahdhiyyah, Husnun (Al-Hukama': The Indonesian Journal of Islamic Family Law, 2021)
Legal marriages according to Islamic law are not necessarily legal according to Dayak customary law. The bride and groom must hold a traditional Dayak wedding ceremony in which there are things that are contrary to Islamic law, such as cutting pigs, wine and begendang party. This study is a qualitative research with symbolic interpretative approach using observation, interviews and documentation in the data collection. Primary data were directly obtained from interviews with religious leaders, Dayak traditional demons and Dayak indigenous people. There are three variants of the views of the Muslim Dayak community on the traditional Dayak Sungai Melayu Rayak wedding ceremony procession, namely: theological normative, sociological normative and sociological empirical. There are two categories and philosophical reasons for the preservation of the traditional wedding ceremony procession by the Dayak religious Leaders and Demong Dayak Adat Melayu Sungai Rayak, namely internal and external. Internal reasons include: the sacredness of marriage, the commitment of marriage, the practice of plurality in the family and the procession of the traditional wedding ceremony that is a culture that needs to be preserved and maintained because it can create inter-religious harmony. While external reasons include: avoiding the moral sanction that is not recognized, social sanctions are excluded, namely economic sanctions imposed fines and the last is controlling. [Perkawinan sah menurut hukum Islam belum tentu sah menurut hukum adat Dayak. Kedua mempelai harus mengadakan upacara pernikahan Adat Dayak yang di dalamnya terdapat hal-hal yang bertentangan dengan syari’at Islam seperti pemotongan babi, pesta tuak dan begendang. Penelitian ini merupakan jenis penelitian Kualitatif dengan pendekatan simbolik interpretatif yang menggunakan teknik pengumpulan data dengan melalui metode observasi, wawancara dan dokumentasi. Sumber data primer yang langsung diperoleh dari wawancara Tokoh Agama, Demong Adat Dayak dan masyarakat adat Dayak. Ada tiga varian pandangan masyarakat Dayak muslim terhadap prosesi upacara pernikahan adat Dayak Sungai Melayu Rayak, yaitu: normative teologis, normative sosiologis dan empiris sosiologis. Ada dua kategori dan alasan filosofis dipertahankannya prosesi upacara pernikahan adat oleh Tokoh Agama dan Demong Adat Dayak Sungai Melayu Rayak, yaitu internal dan eksternal. Alasan internal meliputi: sakralitas perkawinan, komitmen pernikahan, praktek pluralitas di dalam keluarga dan prosesi upacara pernikahan adat tersebut merupakan budaya yang perlu dilestarikan dan dipertahankan karena dapat menciptakan kerukunan antar umat beragama. Sedangkan alasan eksternal meliputi: menghindari sanksi moral yaitu tidak diakui, sanksi sosial yaitu dikucilkan, sanksi ekonomi yaitu dikenakan denda dan terakhir adalah controlling.]